The Anatomy of French Production Hierarchies - Caliendo, Lorenzo; Monte, Ferdinando; Rossi-Hansberg, Esteban (Journal of Political Economy, 2015)
We study the internal organization of French manufacturing firms. We divide the employees of each firm into “layers” using occupational categories. Layers are hierarchical in that the typical worker in a higher layer earns more, and the typical firm occupies less of them. The probability of adding/dropping a layer is positively/negatively correlated with value added. Reorganization, through changes in layers, is essential to understanding how firms grow. Firms that expand substantially add layers and pay lower average wages in all preexisting layers. In contrast, firms that expand little and do not reorganize pay higher average wages in all preexisting layers.